Serological investigation of Equine Viral Arteritis (EVA) in Bulgaria - CHENCHEV, I.; GEORGIEV, G.; YORDANOV, S.; NEDELCHEV, N. (Journal of the Hellenic Veterinary Medical Society, 2017)
The aim of the present study was to estimate the existence of EVA infection in equine's population in Bulgaria. For this purpose the clinical signs of the disease, as well as the antibodies titre against the virus in unvaccinated equines population, were estimated. Out of 1.743 tested non vaccinated animals, 1.425 blood sera were positive for antibodies to EVA, 81.76% positivity, during 2003 - 2007. The positive samples were coming from 14 stables, riding clubs and breeding farms of the country. EVA is considered as a major problem of veterinary importance in Bulgaria during the current and next years.